Analisa Tegangan dan Safety Factor Pada Design Poros Mesin Crusher Untuk HDPE Kapasitas 0.2646 Kg/min - Sandya Gilang Samudra; Oscar Haris (Indie Press, 2025)
Crusher and extruder machines for HDPE plastic materials are used as high density polyethylene (HDPE) plastic waste processing machines to produce plastic pellets. In designing the shaft, it is an important element in the construction of the crusher machine to transmit motor power through the pulley. Based on the design calculation results, the shaft diameter is 30 mm with a length of 392 mm and the shaft torsional moment is 6678.85 Kg.mm. The design results, stress and safety factor in the Finite Element Method (FEM) Solidworks simulation. The research purposes is to avoid shaft design failure. The shaft with AISI 1045 material is the most suitable for the required requirements with a safety factor value of 1.6675 with a maximum known stress value of 315,939,328 N/m2